Diversity of Gender and Formation of Ingroup: a Contribution of Leader - Member Exchange Theory - LMX - Amaral, Derly Jardim do; Godoy, Arilda Schimidt; César, Ana Maria Roux Valentini Coelho; Silva, Adilson Aderito da (Review of Business Management, 2007)
The purpose of this article is to investigate the relationship between the Leader and Member Exchange Theory - LMX´s assumptions and the diversity of genders. To accomplish it, a questionnaire named LMX-MDM developed by Liden and Maslyn (1998) was used. The instrument is composed by 11 propositions that measures the multidimensionality of LMX. The questionnaire was submitted to a reversed translation process and was applied on a sample of students from Universidade Presbiteriana Mackenzie, located in São Paulo. The sample was composed of 241 students, from which 124 (51,5%) men and 117 (48,5%) women. The collected data was submitted to univariate and multivariate techniques, and the results revealed that the researched sample perceives the dimensions of affection, loyalty, contribution and professional respect in line with LMX´s assumptions, and that female gender feel more participant of the ingroup than people from the ale group. Key-words: Diversity. Gender. Leadership.